2016
DOI: 10.1016/j.jaci.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation outcomes for 11 patients with dedicator of cytokinesis 8 deficiency

Abstract: Background Dedicator of cytokinesis 8 (DOCK8) deficiency can be cured by allogeneic hematopoietic stem cell transplantation (HSCT). Reports of outcome are still limited. Objective To analyze the results of HSCT in patients with DOCK8 deficiency and report whether approaches resulting in mixed chimerism result in clinically relevant immune reconstitution. Methods We performed retrospective chart review of 11 patients with DOCK8 deficiency, and measured DOCK8 expression and cytokine production. Results Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 22 publications
6
73
1
1
Order By: Relevance
“…Regarding the extent of donor chimerism necessary to reverse the disease phenotype, a retrospective study of 11 patients with DOCK8 deficiency who underwent HSCT was recently reported [14]. Although the 7 patients receiving matched related donors all had high levels of donor chimerism, several of the mismatched patients, who received a nonmyeloablative regimen, had high levels of donor CD3 + chimerism but low levels of myeloid and B cell chimerism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the extent of donor chimerism necessary to reverse the disease phenotype, a retrospective study of 11 patients with DOCK8 deficiency who underwent HSCT was recently reported [14]. Although the 7 patients receiving matched related donors all had high levels of donor chimerism, several of the mismatched patients, who received a nonmyeloablative regimen, had high levels of donor CD3 + chimerism but low levels of myeloid and B cell chimerism.…”
Section: Discussionmentioning
confidence: 99%
“…DOCK8 deficiency is associated with a high degree of morbidity and mortality—including life-threatening infections and virus-driven malignancies—with an estimated overall survival of 50% at 20 years [3]. Allogeneic hematopoietic stem cell transplantation (HSCT) represents a curative therapy for DOCK8 deficiency [6-14]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…She was started on antimicrobial prophylaxis and monthly IVIG infusion with good clinical improvement. Currently, the patient is being evaluated for hematopoietic stem cell transplantation (HSCT) from her full-matched healthy sibling (23). …”
Section: Resultsmentioning
confidence: 99%
“…Finally, and in terms of therapy, the definitive treatment of DOCK8 deficiency is bone marrow transplantation (23). The emergence of immune dysregulation in the context of an immunodeficiency disorder presents challenges in terms of therapy.…”
Section: Discussionmentioning
confidence: 99%